PENGARUH KERJASAMA TIM, KREATIVITAS DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN CV. RONALD JAYA TRANSPORT PANGKALPINANG - Andriani, Desi; Medinal; Tri Setyo Mulyani, Hendarti (Jurnal Progresif Manajemen Bisnis, 2021)
This research was entitled: “Pengaruh Kerjasama Tim, Kreativitas, dan Budaya Organisasi Terhadap Kinerja Karyawan CV. Ronald Jaya Transport Pangkalpinang”. The background of this research is based on declining employees performance in the company. The purpose of this study was to determine and examine the effect of teamwork, creativity and organizational culture on employee performance, both simultaneously and partially. The method of research is a descriptive quantitative study with a sample size of 56 respondents. This study has three independent variables; teamwork, creativity and organizational culture. The dependent variable was labeled as an employee performance. Testing instruments are using validity and reliability tests. The data analysis method used in this study is Multiple Linear Regression Analysis using the F-test along with Simple Linear Regression with T-test. Also the researcher use an analysis of the Coefficient of Determination (R2) in order to provide empirically the ability to explaining the dependent by three independence variables simultaneously. The results of the research on the independent variable teamwork (X1) obtained t-count 0.307 < t-table .674, creativity variable (X2) with t-count 5.914 > t-table 1.674 and organizational culture variable (X3) with t-count 2.478 > t-table 1.674. Therefore, a teamwork does not have a partial effect towards an employee performance, a creativity has a partial effect towards an employee performance. Also, the study stated if organizational culture also has a partial a partial effect towards an employee performance. The results of the F-test show that F-count 55.644 > F-table 2.78. This means that the independent variables (teamwork, creativity and organizational culture) simultaneously have an affect towards the dependent variable (employee performance). The test results of the Coefficient of Determination (R2) show Adjusted R-Square 0.749 or in other word, that employee performance variable can be explained by variables teamwork, creativity and organizational culture by 74.9%. While the remaining 0.251 or 25.1% can be explained by other variables outside the research variables.